Screening for Hypogonadism in Primary Healthcare: How to do this Effectively - Livingston, Mark; Jones, Richard; Hackett, Geoff; Donnahey, Gemma; Moreno, Gabriela YC; Duff, Christopher J.; Heald, Adrian H. (Experimental and Clinical Endocrinology & Diabetes, 2018)
Background Testosterone, the most important androgen produced by the testes, plays an integral role in male health. Testosterone levels are increasingly being checked in primary healthcare as awareness of the risks of male hypogonadism grows.Aim To investigate what tests are performed to screen for hypogonadism and to exclude secondary hypogonadism.Design and Setting All participants attended general practices in the UK.Methods Data search was performed using the EMIS® clinical database (provider of the majority of GP operating systems in Cheshire). The anonymised records of male patients aged 18–98 years who had undergone a check of serum testosterone during a 10-year period were analysed.Results Overall screening rate was 4.3%. Of 8 788 men with a testosterone result, 1 924 men (21.9%) had a total testosterone level <10 nmol/L. Just 689 of 8 788 men (7.8%) had a sex hormone-binding globulin (SHBG) result, corresponding to 30.5% of those potentially hypogonadal. Estimated free testosterone was negatively associated with BMI (Spearman’s rho -0.2, p<0.001) as was total testosterone in the over 50 s. Of 1 924 potentially hypogonadal men with a serum testosterone <10 nmol/L, 588 of 1 924 (30.6%) had a check of serum prolactin. 46.3% and 41.7% had LH and FSH measured, respectively. Only 19.1% of 1 924 men with a hypogonadal total testosterone level were subsequently put on testosterone replacement. The percentage of men in the relatively socially disadvantaged category was similar for both eugonadal and hypogonadal men with a much higher rate of screening for hypogonadism in more socially advantaged men.Conclusions Screening in primary healthcare identified a significant minority of men who had potential hypogonadism. Interpretation of a low serum testosterone requires measurement of serum prolactin, LH and FSH in order to rule out secondary hypogonadism. We suggest that this becomes part of routine screening with a balanced screening approach across the socioeconomic spectrum.
Keywords: testosterone; hypogonadism; body mass index; screening; disadvantage